2006
DOI: 10.1002/qua.21218
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio computational modeling on the tautomerism of monochalcogenocarboxylic acids CH3C(O)XH (X = S, Se, and Te) in the polar and aprotic solution

Abstract: ABSTRACT:Computational modeling by an ab initio molecular orbital method (HF and MP2) with the 6-311ϩG(d,p) and 6-311ϩϩG(2df,2pd) basis sets on the tautomerism of three monochalcogenocarboxylic acids CH 3 C(AO)XH (X ϭ S, Se, and Te) in the polar and aprotic solution tetrahydrofuran (THF) was undertaken using the combined supramolecular/continuum method, in which CH 3 OCH 3 was considered as a realistic model for THF in the supermolecule. Our calculations showed that the tautomerism involving CH 3 OCH 3 not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Nguyen and coworkers found that the tautomeric barrier of thioformic acid HC(@O)SH in the CH 3 OCH 3 is increased by about 1.5 kcal/mol relative to the reactant complex [7]. Interestingly, the work of Ren et al showed that the tautomerism involving CH 3 OCH 3 not only gives the preference of the enol form in the tautomeric equilibrium, but also significantly lowers the tautomeric barriers by >8 kcal/mol in THF solution [8].…”
Section: Introductionmentioning
confidence: 95%
“…Nguyen and coworkers found that the tautomeric barrier of thioformic acid HC(@O)SH in the CH 3 OCH 3 is increased by about 1.5 kcal/mol relative to the reactant complex [7]. Interestingly, the work of Ren et al showed that the tautomerism involving CH 3 OCH 3 not only gives the preference of the enol form in the tautomeric equilibrium, but also significantly lowers the tautomeric barriers by >8 kcal/mol in THF solution [8].…”
Section: Introductionmentioning
confidence: 95%
“…Recently we used the combined supramolecular/continuum model 1–8 to study the influence of the polar solvent (THF) on the tautomeric equilibrium of monochalcogenocarboxylic acids CH 3 C(O)XH ↔ CH 3 C(X)OH (X = S, Se, Te)9 and modeled more reliably on the performances of the monochalcogenocarboxylic acids in polarized solution, giving some reasonable explanations for the experimental results, i.e., the enol form RC(X)OH predominantly presents in polar solvents at lower temperatures, while the keto form RC(O)XH is preferred in the gas phase or in the nonpolar solvents. As a continued theoretical study on the tautomerism of carboxylic acids, in this article, we present the computational investigations on monochalcogenosilanoic acids CH 3 Si(O)XH (X = S, Se, Te), the silicon analogous of CH 3 C(O)XH.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Some synthetic contributions to aliphatic (R = C n H m with n ! 2) and aromatic selenocarboxylic acids have been made by Kato et al [1][2][3][4] In contrast, carboxylic acids (RC(O)OH) and thiocarboxylic acids (RC(O)SH) are common compounds with a wide range of applications.…”
mentioning
confidence: 99%